2022
DOI: 10.1002/ese3.1102
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and contributing factors of major coal bursts in longwall mines

Abstract: Coal burst has become one of the most serious hazards in longwall coal mines of many countries, and extensive studies have been conducted on the mechanism, prediction, and prevention of coal bursts. However, most of these studies focus on qualitative descriptions of burst environments and specific case analyses. Few studies have been carried out to explore knowledge through a number of past coal bursts in longwall mines. The main objective is to quantitatively analyze the current burst‐prone conditions in long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Some sites of these interfaces represent thin interburdens of carbonaceous rocks or high-ash clayey coals [29,30] with low deformation characteristics and strength properties (for example, cohesion of 0.005-0.2 MPa [31,32]). When the mining front approaches such sites, the stresses change abruptly and the dynamic events take place [27,33,34]. Early detection of such weak zones will enable preventive measures to be undertaken [35] to reduce the risk of the undesirable geodynamic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Some sites of these interfaces represent thin interburdens of carbonaceous rocks or high-ash clayey coals [29,30] with low deformation characteristics and strength properties (for example, cohesion of 0.005-0.2 MPa [31,32]). When the mining front approaches such sites, the stresses change abruptly and the dynamic events take place [27,33,34]. Early detection of such weak zones will enable preventive measures to be undertaken [35] to reduce the risk of the undesirable geodynamic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the maximum stress decreased with increasing temperature, and it increased with an increasing strain rate. These people established the constitutive models required for quantitative analysis based on experimental samples, but these have rarely been combined with CT experiments [9,[12][13][14][15][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%